Strong deep-water formation in Baffin Bay ensured the heavy snowfall that initiated the Last Ice Age in the Northern Hemisphere - Johnson, Robert Glenn (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2021)
The extremely heavy precipitation that initiated the Last Ice Age (the Wisconsin Glaciation in Canada) was caused by a strong and persistent atmospheric low-pressure system centered over the northern Labrador Sea and southern Baffin Bay. This system, called the Labrador Low, was dependent on strong deep-water formation in the northern end of Baffin Bay. The replacement for the sinking deep water consisted of warmer and more saline Irminger Current water that mixed into the northward-flowing West Greenland Current near the center of the Labrador Low. The heavy precipitation in northeastern Canada began after the stratification in Baffin Bay was eliminated by the southward flow of denser Atlantic water through the Nares Strait. This temporary flow began when the oscillating Atlantic Meridional Oceanic Circulation (AMOC) flow reached a maximum greater than today. This sent Atlantic water westward, north of Greenland and through the Nares Strait. Although the extremely heavy snowfall began the Wisconsin Glaciation in Canada, the initiation of the Last Ice Age in Eurasia was a more complex process and was delayed by about 4,000 years by formation of the Hudson Strait ice dam.